[Rezension von: Michael Sokoloff, A dictionary of Judean Aramaic] - Beyer, Klaus (Journal of Semitic studies, 2006)
A Dictionary of Judean Aramaic Michael Sokoloff Bar-Ilan University Press, Ramat Gan 2003. 88. Price: $25.00 hardback. ISBN: 965-226-261-7.
Online veröffentlicht: 1. März 2006
Keywords: Rezension